(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
Starting from the understanding of the Triangular Approach as a way to elaborate worlds based on the interpretation of images and artistic objects, an art / educational activity developed during the vacation course of the year 2020 will be presented, at the Escolinha de Arte do Recife (EAR), in order to record how the institution has been operating in the contemporary world. First, we will make a historical contextualization of the institution’s emergence, from its pedagogical perspectives, and then reflect on the artistic activity of stamping with alternative materials, the contributions to the aesthetic formation of children. Following artistic methods used by the artist Iza do Amparo, an artist presented during a vacation course module, the children, as will be seen, when coming into contact with the artist’s work and with the artist herself, were able to expand their aesthetic perceptions, and capacity for reflection on topics such as: Ethics, Environment and Local Culture.